Molecular evidence of Borrelia theileri and closely related Borrelia spp. in hard ticks infesting domestic animals - Khan, Mehran; Almutairi, Mashal M.; Alouffi, Abdulaziz; Tanaka, Tetsuya; Chang, Shun-Chung; Chen, Chien-Chin; Ali, Abid (Frontiers in Veterinary Science, 2023)
Ticks pose significant threats to hosts by transmitting Borrelia spp., which are grouped into Lyme borreliae, relapsing fever borreliae (RF), and reptiles- and monotremes-associated borreliae. The RF borreliae encompass a group of Borrelia species predominantly transmitted by soft ticks, but some of its members can also be transmitted by hard ticks. Information on the detection and genetic characterization of tick-borne RF borreliae, including Borrelia theileri, is notably rare in Asia, particularly in Pakistan. Herein, we employed molecular techniques to detect borreliae in hard ticks collected from domestic animals in Khyber Pakhtunkhwa, Pakistan. Ticks were subjected to morphological analysis, followed by DNA extraction and PCR amplification of partial fragments of borrelial 16S rRNA and flaB genes. A total of 729 ticks were collected from 264 hosts, with Haemaphysalis cornupunctata (12.9%; 94/729) being the most prevalent, followed by Hyalomma anatolicum (11.7%; 85/729), Rhipicephalus microplus (10.0%; 73/729), Haemaphysalis kashmirensis (9.1%; 66/729), Haemaphysalis bispinosa (8.5%; 62/729), Rhipicephalus sanguineus (8%; 58/729), Haemaphysalis montgomeryi (6.2%; 45/729), Rhipicephalus turanicus (5.5%; 40/729), Hyalomma dromedarii and Ixodes kashmirensis (4.4%; 32/729 each), Rhipicephalus haemaphysaloides (4.1%; 30/729), Haemaphysalis sulcata and Hyalomma scupense (3.8%; 28/729 each), Haemaphysalis danieli (2.9%; 21/729), Hyalomma kumari (2.6%; 19/729), and Hyalomma isaaci (2.2%; 16/729). Based on 16S rRNA detection of Borrelia spp., only R. turanicus yielded positive results, resulting in an overall infection rate of 0.3% (2/160), while using flaB-based detection, four tick species including R. microplus, R. turanicus, Ha. sulcata, and Ha. cornupunctata showed positive results, yielding an overall infection rate of 6.9% (11/160). The amplified DNA fragments of borrelial 16S rRNA and flaB in R. turanicus from goats shared maximum identities of 100% and 99.40% with Borrelia theileri, respectively. Amplified borrelial flaB fragments in R. microplus from cows and sheep displayed 100% identity with B. theileri, while flaB fragments in Ha. cornupunctata and Ha. sulcata from goats revealed identities of 99.32% and 99.75% with undetermined RF Borrelia spp., respectively. Phylogenetic analysis revealed clustering of B. theileri from R. microplus and R. turanicus with the same species, while Borrelia spp. from Ha. cornupunctata and Ha. sulcata with undetermined RF Borrelia spp.